APPLICATION OF A VIBRATING MACHINE FOR RECEIVING AMMONIA WATER FOR PLANT FEEDING - DUSHENKO, OLEKSANDR; TKACHUK, VITALIY (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Inadequate water treatment for boilers and impurities present in untreated water lead to a number of problems: large colloidal and mechanical impurities in the form of scale, rust, clay or sand quickly clog pipes, significantly reducing their internal diameter. Based on the analysis of recent studies, it is proposed to improve the quality and composition of water that comes from municipal water supply, artesian wells and reservoirs, before filtering and deaeration of water, it is proposed to pre-treat it with hydrocavitation and a magnetic field in order to soften and change its properties. This leads to the failure of shut-off valves and pumping equipment: hardness salts and other poorly soluble salts (carbonates, sulfates of magnesium and calcium, silicates, various compounds of copper and manganese) settle, forming a crust on the metal walls of the equipment, which reduces its heat output. This contributes to a reduction in boiler power, an increase in electricity costs, and significantly shortens the service life of the equipment. The essence of the proposed equipment is that the effect of hydrocavitation and a variable magnetic field on water is reduced to a single process - the splitting of water molecules in the cavitation cavity into active radicals. The essence of the process of hydrocavitation on the course of chemical reactions, the breaking of hydrogen bonds in water molecules is considered. The design of a vibrating machine with an additional hydrocavation effect on water during the reciprocating movement of the liquid through the nozzle is proposed, which increases the total effect of breaking hydrogen bonds in water molecules, oxidizing iron and calcium ions, increasing the pH value, and after settling, it enters the ion exchange and deaeration plant, and later to the heating network.
Keywords: productivity; vibration machine; hydrocavitation; drive parameters